2020
DOI: 10.3390/genes11020133
|View full text |Cite
|
Sign up to set email alerts
|

ALT: A Multi-Faceted Phenomenon

Abstract: One of the hallmarks of cancer cells is their indefinite replicative potential, made possible by the activation of a telomere maintenance mechanism (TMM). The majority of cancers reactivate the reverse transcriptase, telomerase, to maintain their telomere length but a minority (10% to 15%) utilize an alternative lengthening of telomeres (ALT) pathway. Here, we review the phenotypes and molecular markers specific to ALT, and investigate the significance of telomere mutations and sequence variation in ALT cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Telomeres are nucleoprotein complexes that consist of a tandem 5'-TTAGGG-3' sequence and protect the ends of eukaryotic chromosomes, preventing DNA damage response (DDR), end-to-end fusions and genomic instability [1]. Telomeric DNA ranges from 3 to 15 Kb in humans, leaving a G-rich 3'-single-strand extended beyond the complementary chain, usually called the G-overhang [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Telomeres are nucleoprotein complexes that consist of a tandem 5'-TTAGGG-3' sequence and protect the ends of eukaryotic chromosomes, preventing DNA damage response (DDR), end-to-end fusions and genomic instability [1]. Telomeric DNA ranges from 3 to 15 Kb in humans, leaving a G-rich 3'-single-strand extended beyond the complementary chain, usually called the G-overhang [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres are nucleoprotein complexes that consist of a tandem 5'-TTAGGG-3' sequence and protect the ends of eukaryotic chromosomes, preventing DNA damage response (DDR), end-to-end fusions and genomic instability [1]. Telomeric DNA ranges from 3 to 15 Kb in humans, leaving a G-rich 3'-single-strand extended beyond the complementary chain, usually called the G-overhang [1,2]. To avoid the end-protection problem due to the overhang chain, the G-tail folds into itself, invading the double-stranded telomeric DNA, forming a lasso-like structure called the t-loop [3], which is protected by a six protein complex called shelterin [4], essential for telomere replication and regulation [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, telomeric DNA in ALT+ cells is constantly elongating, showing that its telomeres rely on recombining mechanisms like homologous recombination (HR) and homology-directed repair (HDR) pathways to be extended 5,6. ALT+ cells also show heterogenous telomere length, abundant extrachromosomal repeats (ECTRs), telomere sister chromatid exchange (T-SCE) 7 and high levels of extrachromosomal telomeric single-stranded DNA known as C-circles, which are markers for ALT+ cells detection 8. The main characteristic of ALT+ telomeres is its association with promyelocytic leukemia (PML) proteins, which altogether are believed to function as platforms for telomere recombination and are known as ALT-associated PML bodies (APBs) 7,9. In fact, it has been shown that disruption of APBs blocks the ALT mechanism 7. Although, many proteins have been implicated in the ALT mechanism, like the loss of alpha thalassemia/mental retardation syndrome X-linked chromatin remodeler (ATRX), the loss of histone chaperone death domain-associated protein (DAXX) and histone H3.3 (H3F3A) and the well-known expression of RAD51/52 complex, the molecular basis through which ALT occurs remain elusive and poorly understood 1,5,10. Many anti-telomerase-based cancer therapies used in cancer treatment, are believed to cause the switching in some tumors from telomerase to ALT 3,11. Indeed, the co-existence of telomerase and the ALT mechanism has been reported in some cancer types 3,12. This switching has converted ALT in a potential target for therapy in the last years, due to the poor prognosis these cells represent 1,7,13. Different drugs have been tested in the last years to target ALT+ cells, however, most of them have been unsuccessful or are on phase 1/2 of clinical trials1,7.…”
Section: Introductionmentioning
confidence: 99%